Use Of Mobile Health In Care Management Hypertension Patients: Literature Study - Novan Kurniawan; Sukihananto (Essential English Grammar, 2022)
Hypertension is the major caused of cardiovascular mortality in the world and in Indonesia, hypertension is the riskfactor of cardiovascular disease such as heart failure, chronic kidney disease, diabetes mellitus, and stroke. Currenttechnology improvement bring so many development information system refers patient monitoring and healthcare incertain community groups. Healthcare and health promotion who take advantage of mobile technology also known as mHealth. . This study uses a non-systematic literature review method based on relevant sources from related topics to beable to provide an overview of the use of mobile health in the management of hypertension control. Based on the resultsof a review of 7 research articles, it can be concluded that the use of mobile health applications is effective in managinghypertension disease control. 6 out of 7 of research shows that the use of mobile health has a significant effect onmanagement of hypertension patient care. Based on the result of f a review of 7 research articles, it can be concludedthat the use of mobile health applications is effective in managing hypertension control